Radio after the golden age the evolution of American broadcasting since 1960 - Cox, Jim 1939- (McFarland, 2013)
"What became of radio after its Golden Age ended about 1960? Much has transpired.Disc jockeys, narrowcasting, the FM band, satellites, automation, talk, ethnicity, media empires, Internet streaming, and gadgets galore. Deregulation, payola, HD radio, pirate radio, fall of transcontinental networks, the rise of local stations, conglomerate ownership, and radio's future landscape are examined in detail"..
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1960-2013; Geschichte; Radio broadcasting -- United States -- History -- 20th century; Radio broadcasting -- United States -- History -- 21st century; Hörfunk; USA